2013
DOI: 10.5007/2175-7925.2013v26n4p167
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia da língua e características das papilas linguais de Cuniculus paca (Rodentia: Cuniculidae)

Abstract: Submetido em 18/03/2013 Aceito para publicação em 02/09/2013 ResumoEste artigo descreve a morfologia da língua, seus músculos extrínsecos e as características das papilas linguais de Cuniculus paca. Foram utilizados quinze espécimes provenientes do Setor de Animais Silvestres da Universidade Estadual Paulista (UNESP). Nessa espécie, a língua se divide em três regiões: raiz, corpo e ápice. Este último é delimitado pelo frênulo lingual, que possui aspecto de membrana fibrosa. Identificou-se também um sulco media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
4
3
1
Order By: Relevance
“…Previos studies have reported that conical papillae are located in the middle of the root of the tongue in hazel dormouse (23) and on the intermolar prominence of the root of the tongue in rock cavy (28) and degu (29). The distribution of conical papillae on the tongues of Japanese lesser flying squirrel (17), Jentink's flying squirrel (18) and paca (25) were similar to our study findings. The presence of a thick keratinized layer detected on the epithelial surface of the conical papillae in this study was consistent with the expression of a keratinized layer on the surface of the conical papilla epithelium of tongues in the Jentink's flying squirrel (18) and rock cavy (28).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previos studies have reported that conical papillae are located in the middle of the root of the tongue in hazel dormouse (23) and on the intermolar prominence of the root of the tongue in rock cavy (28) and degu (29). The distribution of conical papillae on the tongues of Japanese lesser flying squirrel (17), Jentink's flying squirrel (18) and paca (25) were similar to our study findings. The presence of a thick keratinized layer detected on the epithelial surface of the conical papillae in this study was consistent with the expression of a keratinized layer on the surface of the conical papilla epithelium of tongues in the Jentink's flying squirrel (18) and rock cavy (28).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, five types of tongue papillae filiform, conical, fungiform, vallate and foliate were detected on the tongue of the squirrel. The shape and distribution of these papillae were similar to the papillae found on the tongue of rats (8), Japanese lesser flying squirrel (17), Jentink's flying squirrel (18), hazel dormouse (23) and paca (25). Filiform papillae were a common and abundant type of papillae on the tongue, extending from the apex to the root.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…On the other hand, the conical-shaped papillae of the desert hedgehog were distributed on the distal part of the tongue in the small triangular area between the linguae radix in between the three circumvallate papillae, while the distal part was devoid of that type. Similar observations were reported in the lowland paca (Machado et al, 2013), leopard (Sadeghinezhad et al, 2017), and ocelot (Freire et al, 2019). However, the conical-shaped papillae in desert hedgehogs undergo numerous processes and this feature is unique and has not been described before.…”
Section: Discussionsupporting
confidence: 83%
“…While the lingual root was devoid of the fungiform type, similar observations were recorded in the long‐eared hedgehog (Parchami et al, 2018). Similar papillary arrangements were reported in rabbits even though they are herbivores (Beraldo‐Massoli et al, 2013). The spatial distribution of fungiform papillae varies among mammalian species.…”
Section: Discussionsupporting
confidence: 80%